ANALYSIS OF SPEAKING ANXIETY ON VOCATIONAL HIGH SCHOOL STUDENTS IN ENGLISH PERFORMANCE - Haninda, Viola; Rahmah, Leny Saili; Hidayat, Hamdan (TELL - US JOURNAL, 2025)
Many EFL students feel that speaking in English is the most difficult skill, So this triggers the emergence of speaking anxiety among students. This study aims to analyze the level of anxiety in speaking English as well as the factors that influence speaking anxiety among the 11th grade students of SMKN 1 Stabat. The study used a qualitative approach with random sampling technique in class XI of Beauty and Spa Management which totaled 27 students. Google Form was used to distribute the questionnaire, which is based on the Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz et al. (1986) and has 31 question items formatted in a five-point Likert scale. Data were analyzed using Microsoft Excel 2007, along with interviews and observations. The majority of students reported experiencing moderate levels of anxiety, with test anxiety being the most common.  According to Horwtz et al. (1986), the elements of student speaking anxiety are divided into three categories: test anxiety, communicative fear, and fear of receiving poor judgment. A homogeneous and supportive learning environment, where all students come from the same major and gender, plays an important role in reducing anxiety levels. The negative impact of anxiety on students' speaking performance was not significant as students were able to manage their anxiety well. This finding confirms the importance of creating a conducive learning environment to increase students' confidence and active participation in English language learning.